Age-related differences in functional hamstring/quadriceps ratio following soccer exercise in female youth players: An injury risk factor - De Ste Croix, M.; Priestley, A.; Lloyd, R.; Oliver, J. (Pediatric Exercise Science, 2018)
Purpose: Fatigue negatively alters dynamic knee control, and the functional hamstring/quadriceps ratio (H/QFUNC) plays an important role in stabilizing the joint. The aim of this study was to investigate the influence of soccer-specific exercise on H/QFUNC in under (U) 13-, U15-, and U17-year-old female soccer players. Methods: A total of 36 female players performed concentric and eccentric actions of the hamstrings at 60°, 120°, and 180°/s before and after an age group-specific field-based soccer protocol. H/QFUNC was determined in the first 30° of knee flexion. Results: Significant angle×velocity (P?=.001) and time×angle (P=.033) interaction effects were found indicating a lower H/QFUNC with increased movement velocity at 0°-10° as opposed to greater knee flexion angles. Fatigue-related effects were only evident near full knee extension. Probabilistic inferences indicated that changes in H/QFUNC were generally unclear in U13s, likely detrimental in U15s, and very likely beneficial in U17s. Conclusions: Altered muscular control following soccer-specific exercise is age dependent with players` 1-year post-peak height velocity at greatest risk of injury. Injury prevention and screening need to be age and maturation appropriate, should consider the effects of fatigue, and include movements near full extension.